EFFECTIVENESS OF THE FIRST CLASS APPLIANCE FOR DISTAL MOVEMENT OF MAXILLARY PERMANENT MOLARS IN CHILDREN WITH ERUPTED SECOND PERMANENT MOLARS - Skrypnyk, І.L.; Shnaider, S.A.; Gorokhivskiy, V.N.; Dienga, A.E.; Suslova, O.V.; Kordonets, O.L.; Lysenko, V.V. (World of Medicine and Biology, 2025)
The study was devoted to evaluating the effectiveness of the First Class Leone appliance for distal movement of the first permanent molars of the upper jaw in children who have erupted second permanent molars. This study included a total of 10 patients aged 8–13 years who presented with a distal relationship of the maxillary first permanent molars and fully erupted second permanent molars, as confirmed by clinical examination and radiographic evaluation. The First Class Leone appliance was used for the distal movement of the permanent molars of the upper jaw. The maxillary first permanent molars were successfully distalized by an average of 4.29±0.36 mm, at a rate of 1.04 mm/month, demonstrating the reliability of the First Class Leone appliance in cases where second permanent molars are already present.
Keywords: anomalies of the dentition; First Class Leone appliance; molar distalization; orthodontic treatment; children